Knowledge Map : Impact of ICTs on Learning and Achievement - World Bank (World Bank, Washington, DC, 2012)
It is generally believed that information and communication technologies (ICTs) can empower teachers and learners, promote change and foster the development of '21st century skills, but data to support these beliefs are still limited. There is widespread belief that ICTs can and will empower teachers and learners, transforming teaching and learning processes from being highly teacher-dominated to student-centered, and that this transformation will result in increased learning gains for students, creating and allowing for opportunities for learners to develop their creativity, problem-solving abilities, informational reasoning skills, communication skills, and other higher-order thinking skills. However, there are currently very limited, unequivocally compelling data to support this belief.